Instagram educators in Latin America. An approach to their practices and potential - Beltrán-Flandoli, Ana; Rivera-Rogel, Diana; Córdova-Tapia, Rebeca; Tejedor, Santiago (Frontiers in Education, 2025)
IntroductionInstagram, a visually-driven platform preferred by 85% of global influencers, remains underutilized in the educational domain. In Latin America, a region marked by socio-technological contrasts, the emergence of educational content creators—or “edugrammers”—has gained momentum, yet little is known about their strategies and impact. This study explores how these microinfluencers shape informal learning through Instagram.MethodsA descriptive and exploratory study with a mixed-methods design was conducted, grounded in digital ethnography. The research involved mapping 2,318 Instagram profiles using manual extraction, Python, and Talend algorithms, refining the dataset to 2,214. A final sample of 14 Latin American edugrammers was analyzed based on audiovisual, discursive, and engagement characteristics.ResultsThe selected edugrammers collectively reach over 2.28 million followers and predominantly publish content in Arts and Humanities, Education, Engineering, and Social Sciences. They favor reels and visually compelling formats, incorporating platform affordances such as questions, emojis, calls to action, and personalized storytelling. Their audiovisual material reflects high levels of narrative consistency, resolution quality, and user engagement strategies.DiscussionThe findings reveal the emergence of a new educational microinfluence dynamic. Edugrammers leverage Instagram’s communicative tools to establish informal yet impactful pedagogical relationships. However, underused resources like humor and expert collaborations present opportunities for future growth. The study highlights the value of interdisciplinary digital literacies and media pedagogies in strengthening these educational ecosystems.ConclusionThis research provides a foundational model for understanding edugrammers in Latin America as transformative agents in informal digital education. Their content strategies, platform use, and pedagogical engagement reflect evolving instructional trends that merit further exploration and integration into broader educational practices.